The Holy See’s efforts towards reconciliation (Economic and Political Thought, 2016)
The Holy See uses two kinds of diplomacy in international relations – classical(similar to that used by each state) and so-called ‘track two’ diplomacy(specific for non-state actors). In both cases the most important ‘interest’ ofCatholic Church remains ensuring its followers the freedom of practice ofreligion, which at the same time serves to disseminate the religious freedomall over the world. Reconciliation is a part of the Vatican strategy of the‘purification of memory’ that was proposed to the international communityby John Paul II. But only by keeping its own basic principles, which are truth,justice, forgiveness and reconciliation, the strategy can give real and sustainablepeace in the world.